Comparative ex vivo and in vitro Permeation Kinetics of Tocopherol in Liquid Formulations - Nada, Aly (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: There is a growing interest to save animals and cost in transdermal permeation studies, especially during the early screening phase of formulation development. The objective of this study was to establish a relationship between permeability of tocopherol (T) through synthetic and animal membranes and to predict ex vivo data from synthetic membrane results. Materials and Methods: The permeability of T from different liquid formulations (T1-T13) was studied using Spectra/Por® and neonatal rat skin. Isopropyl myristate (ISPM), polyethylene glycol 400 (PEG)-ethanol (1:1 v/v), ethanol, and propylene glycol (PG) were tested individually as carriers, as well as mixtures with dimethyl sulfoxide (DMSO) and tocopheryl polyethylene glycol succinate (TPGS) as solubility and permeation enhancers. The permeation study was conducted in Franz diffusion cells over 24 h. The permeability coefficient (Ps) was calculated from the observed flux value (J). Good correlation was observed for the in vitro and ex vivo studies regarding J and Ps values. Results: The calculated Ps and J from the ex-vivo study were in-line with the corresponding values calculated from Spectra Por® (r = 0.84 and 0.82, for Ps and J, respectively) and followed the same order. The effect of vehicles tested on the permeation of T followed the same rank: PG> ethanol> PEG-ethanol> ISPM, for both the animal and synthetic membrane. The predicted Ps and J values for the neonatal rat skin, based on the correlation with Spectra Por®, followed also the same rank order, yet not the same observed values. Conclusion: Spectra Por® could serve as a good surrogate for the animal skin models for drug permeation studies during the early formulation and screening phase.